การผลิตต้มส้มไก่ตำรับหลวงพระบางจากเนื้อไก่ประดู่หางดำเชียงใหม่พร้อมบริโภคในบรรจุภัณฑ์อ่อนตัวด้วยกระบวนการทางความร้อน - ผไทพิจิตร ดาลาวงศ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aimed to develop ready-to-eat Luang Prabang style sour chicken soup from the meat of Pradu Hangdam Chiang Mai by using small scale thermal processing. Experimental results revealed that the portion of chicken meat of 30 % (w/w) to that of liquid food in the packaging was appropriated. Heat delivery methods by means of boiling or steaming, and also the sizes of packaging (250 and 500 g) were generally not affected the qualities of the product. However, the heat penetration rate provided by steaming was higher than that of boiling. F0 value for the product was found to be 6.46 minute and the qualities of the processed product under this condition were acceptable and microbiology safe for consumption according to related products of Thai standards for small enterprise product.